Answer:
x + 10
Step-by-step explanation:
![(x + 6) - 5 + 9 \\ = x + 6 + 4 \\ = x + 10](https://tex.z-dn.net/?f=%28x%20%2B%206%29%20-%205%20%2B%209%20%5C%5C%20%20%3D%20x%20%2B%206%20%2B%204%20%5C%5C%20%20%3D%20x%20%2B%2010)
Since 6 is positive, it's (x+blank)^2
6/2=3, and (x+3)^2 = x^2+6x+9. We have x^2+6x-2, so we have to add 9 to both sides to get (x+3)^2-2=9, then subtract 9 from both sides to get
(x+3)^2-11=0, or (x+3)^2=11. Square root both sides to get x+3=sqrt(11), and x=sqrt(11)-3, which is approximately 0.32
Answer:
D. f(t) = 192,345(1.04)^t
Step-by-step explanation:
<em>I took the test and it was right. </em>
Also that is the original price and when you look at exponential functions, the starting point or original price is always first the then rate of increase. The table just shows how it increased in year 1 and 2.
Hope this helps. :)
Answer: x = -12 is the correct answer
Step-by-step explanation: the moderator that deleted this if is so wrong then just tell me why is wrong if you are so smart.